(untitled) (Publicaciones en Ciencias y Tecnología, 2017)
Point stochastic processes represent a very useful tool for the analysis of hazard factors in wildfire. In this article, the occurrence of wildfire is studied from a spatial-temporal Poisson process, in which the intensity function thereof is considered as a wildfire hazard characterization based on parametric and non-parametric techniques. Finally, it is considered a set of real data, provided by the Ministerio del Poder Popular para el Ambiente from Instituto Nacional de Meteorología e Hidrologia (INAMEH) of Venezuela, relating to widlfire produced on a particular day. The hazard functions are estimated based on the proposed model and wildfire hazard maps are generated, which are adjusted to the geographical and climatic characteristics of the country.